Análisis de referentes para determinar las competencias de un magister en administración en Colombia - Jennifer Andrea Lemus Quintero; Gladys Castañeda Vergel; Nasly Jesuris Bermúdez Silva (Mundo Fesc)
This article aims to analyze benchmarks to determine the competencies of a Master's in Administration in Colombia, taking into account the requirements of the Ministry of National Education regarding the Higher Education Quality Assurance System, as contemplated in Decree 1330 of July 25, 2019. The work began with a documentary review of the aforementioned regulations; then, various entities related to the science of administration and that represent authority on the subject were investigated, including a roundtable discussion with regional business leaders. Finally, each benchmark was compared using the methodology of the Institutional Policy on Learning Outcomes of the Francisco de Paula Santander Ocaña University. Regional, national, and international expectations regarding the generic and specific competencies that a Master's in Administration graduate should possess from Higher Education Institutions correspond to those that pertinently respond to the country's social, political, economic, environmental, and cultural demands.